PO-50 - The effect of tissue factor expression on colorectal cancer cell proliferation. Issue 140 (April 2016) - Clouston, H.W.; Lamb, R.; Duff, S.; Kirwan, C.C.
Abstract : Introduction: Tissue factor (TF) is abnormally expressed in many cancers including colorectal and is associated with a poor cancer prognosis. Colorectal cancer cell lines expressing TF produce faster growing tumours. In lung cancer, TF inhibition has been shown to reduce proliferation Aim: We aimed to determine if TF expression and activity increases cellular proliferation in colorectal cancer cell lines. Materials and Methods: DLD-1 and SW620 colorectal cell lines were transduced with cDNA to over express TF (TF + ve). Proliferation was determined by Alamar blue assay where level of absorption indicates the number of living cells, expressed as an arbitrary unit of absorption (u). Factor VIIa (TF ligand) at increasing concentrations was used to determine the effect of TF activity on proliferation. Downstream marker of TF activity (MAPK phosphorylation) was assessed by Western blot and correlated with proliferation. Results: There was a significant increase in proliferation in both DLD-1 TF + ve and SW620 TF + ve compared to their negative controls at 42 hours (DLD1 TF + ve: 5, 455u (SD 2, 485u) vs 2, 246u (SD 1, 107u) p < 0.001); SW620 TF + ve: 414u (SD 96u) vs 286u (SD 114u) p < 0.05). When factor VIIa (FVIIa) was added in concentrations from 0 nM to the supra-physiological concentration of 25 nM there was a dose-dependent increase in proliferation up to physiological levels (0.1 nM) which was further increased in the TF + ve cell lines. Fold change from baseline 0 vs 0.1 nM FVIIa (DLD-1: 3.22u (SD 0.61u) vs 6.17u (SD 2.21u) p < 0.05; SW620 2.33u (SD 2.21u) vs 4.69u (SD 0.61u) p < 0.05). The increase in proliferation was reflected in the phosphorylation of MAPK which was increased by TF overexpression alone and further increased by FVIIa in a dose-dependent fashion. Conclusions: Increased TF expression and activation is associated with increased cellular proliferation. This effect appears to be exerted via MAPK pathways. Tissue factor may provide a therapeutic target in colorectal cancer.